PENGEMBANGAN BUKU TEKS PERADABAN JEMBATAN BERBASIS PJBL UNTUK PENGUATAN KARAKTER KONTROL DIRI - Vicensia Araya Reinita; Nugrahanta, Gregorius Ari (Jurnal Muara Pendidikan, 2025)
The low level of self-control among elementary school students poses a fundamental challenge in character education, requiring innovative pedagogical interventions. This study aims to develop the Bridge Civilization textbook based on Project-Based Learning (PjBL) as a strategic medium to strengthen students’ self-control character. Employing a Research and Development (R&D) approach, the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) was applied. The study involved two groups: an experimental group (n = 24) applying the PjBL model and a control group (n = 25) using the lecture method. Research instruments included summative tests (pretest–posttest) for both groups and formative tests for the experimental group only. Expert validation indicated the textbook achieved a “very good” rating (M = 3.78) with no revisions required. The Mann–Whitney U test showed a significant difference in self-control between the control (15,20%) and experimental groups (45.00%), with a large effect size (r = 0.772). N-gain scores indicated low effectiveness for the control (23.85%) and moderate for the experimental group (66.56%). Interrater reliability testing yielded an average α = 0.760 (high category). These findings confirm that the PjBL-based textbook is effective in enhancing elementary school students’ self-control character.